Antibacterial activity of amoxicillin in vitro and its oral bioavailability in broiler chickens under the influence of 3 water sanitizers. (22nd June 2018) - Ledesma, C; Rosario, C; Gracia-Mora, J; Tapia, G; Gutiérrez, L; Sumano, H
ABSTRACT: The interaction of 3 water sanitizers (sodium hypochlorite, iodine-polyvinylpyrrolidone, and citrate) utilized in poultry production on antibacterial activity and bioavailability of amoxicillin trihydrate (AMX ) were studied. Sanitizers were mixed with AMX in prepared water, the resulting substances were regarded as amoxicillin-sanitizer products (ASP ). First, the in vitro antibacterial activity of each ASP was compared to that of AMX. Then, pharmacokinetics (PK ) of ASP and AMX diluted in prepared water, were carried out in broiler-chickens. Amoxicillin or ASP (20 mg/kg) from different concentrations of sanitizers was directly placed into the chicken's crop and blood samples were taken. Basic PK parameters were obtained. Serum activity/concentrations of AMX were assessed by agar diffusion and corroborated with high performance liquid chromatography. Results show that ASP of AMX/sodium hypochlorite decrease both, the antimicrobial activity of in vitro AMX and its relative bioavailability (Fr ) assessed with the maximum serum concentration (Cmax ), the area under the concentration-time curve, and the mean residence time (MRT ) (3.80 μg/mL, 2.70 μg/mL·h, and 0.59 h, respectively), compared to the AMX administered alone (12.54 μg/mL, 44.02 μg/mL·h, and MRT 2.78 h). ASP from amoxicillin/ionophore, reduced the Cmax (10.62 μg/mL), Fr (94.67%), and MRT (2.07 h), at the highest tested concentrations. In contrast, the 2 highest concentrations of the citrate sanitizer increased the Cmax (15.07 and 15.47 μg/mL), Fr (119 and 132%), and MRT (3.32 and 4.06 h) and their in vitro antimicrobial activity. Interactions between the tested water sanitizers and AMX modify the Cmax, Fr, MRT of the latter, altering the PK/pharmacodymanic ratios for a time-dependent antibiotic. Results also reveal that the use of amoxicillin trihydrate administered through the drinking water does not meet the required PK/pharmacodymanic ratios. Thus, it is here postulated that this antibiotic should be administered at least twice a day and that its interaction with water sanitizers should be considered.